2019
DOI: 10.1186/s13012-019-0906-2
|View full text |Cite
|
Sign up to set email alerts
|

Training in Implementation Practice Leadership (TRIPLE): evaluation of a novel practice change strategy in behavioral health organizations

Abstract: Background Effective leadership for organizational change is critical to the implementation of evidence-based practices (EBPs). As organizational leaders in behavioral health organizations often are promoted from within the agency for their long-standing, effective work as counselors, they may lack formal training in leadership, management, or practice change. This study assesses a novel implementation leadership training designed to promote leadership skills and successful organizational change s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 21 publications
2
67
0
Order By: Relevance
“…Of the 41 D&I CBIs identified, a range of ‘types’ of training (as defined by the authors of each of the included articles) were reported including training Institutes ( N = 4) [ 18 a , 48 , 57 , 92 , 103 , 106 , 107 , 109 , 110 c ] or courses that were part of training programmes ( N = 2) [ 18 b , 98 , 100 ] or training initiatives ( N = 1) [ 99 ]; workshops ( N = 4) [ 49 , 93 , 95 , 111 ], seminars ( N = 3) [ 90 a , 110 a,b ], clerkships ( N = 1) [ 88 ], mentorship programmes ( N = 1) [ 90 b ], graduate certificates ( N = 1) [ 89 ], webinars ( N = 1) [ 90 c ], fellowship programmes ( N = 1) [ 97 ], master’s programmes ( N = 1) [ 102 ] or modules that have been integrated in master’s programmes—including clinical research ( N = 1) [ 104 a ] primary health care ( N = 1) [ 105 ] and public health ( N = 1) [ 62 ]; or PhD programmes ( N = 1) [ 94 ] or modules that are integrated as part of a Doctors of Nursing programme ( N = 2) [ 101 , 108 ]. The 15 remaining CBIs were termed by the authors as ‘courses’ relating (in part or in full) to D&I science [ 18 c,d , 47 , 58 , 91 , 96 , 104 b,c , 110 d-k ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 41 D&I CBIs identified, a range of ‘types’ of training (as defined by the authors of each of the included articles) were reported including training Institutes ( N = 4) [ 18 a , 48 , 57 , 92 , 103 , 106 , 107 , 109 , 110 c ] or courses that were part of training programmes ( N = 2) [ 18 b , 98 , 100 ] or training initiatives ( N = 1) [ 99 ]; workshops ( N = 4) [ 49 , 93 , 95 , 111 ], seminars ( N = 3) [ 90 a , 110 a,b ], clerkships ( N = 1) [ 88 ], mentorship programmes ( N = 1) [ 90 b ], graduate certificates ( N = 1) [ 89 ], webinars ( N = 1) [ 90 c ], fellowship programmes ( N = 1) [ 97 ], master’s programmes ( N = 1) [ 102 ] or modules that have been integrated in master’s programmes—including clinical research ( N = 1) [ 104 a ] primary health care ( N = 1) [ 105 ] and public health ( N = 1) [ 62 ]; or PhD programmes ( N = 1) [ 94 ] or modules that are integrated as part of a Doctors of Nursing programme ( N = 2) [ 101 , 108 ]. The 15 remaining CBIs were termed by the authors as ‘courses’ relating (in part or in full) to D&I science [ 18 c,d , 47 , 58 , 91 , 96 , 104 b,c , 110 d-k ].…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen CBIs were delivered face-face [ 47 49 , 88 , 91 , 95 , 100 – 104 a , 106 , 107 , 110 a-c,i,k , 111 ], 7 were delivered remotely (either online, over the phone or through video-conferencing) [ 62 , 90 a-c , 105 , 110 a,b ], 8 were blended—employing F-F and remoted-based methods [ 18 a,b , 57 , 58 , 89 , 92 , 96 98 , 108 , 109 ], 4 were delivered either F-F or remotely (i.e. individuals picked one mode of delivery) [ 93 , 110 e,f,h ] and for the remainder, it was not reported/not clear ( N = 8) [ 18 c,d , 94 , 104 b,c , 110 d,g,j ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As this treatment system must withstand funding uncertainty, limited technical resources and workforce development needs [1, 5,6], program managers require unique leadership approaches. Training managers to develop their leadership capacity to help their staff implement EBPs with fidelity has become a unique feature to improve effectiveness needs in this system [53].…”
Section: Resultsmentioning
confidence: 99%